Proceedings of the Proceedings of the 1st International Conference on Environmental Science and Sustainable Development, ICESSD 2020
DOI: 10.4108/eai.22-10-2019.2291463
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable fisheries subsidies for small scale fisheries in Indonesia

Abstract: As a country with enormous fisheries resources, Indonesia face threats to sustainability of the resources which are suspected because of the implementation of fisheries subsidies that did not consider the resources. On the other side, government provide subsidies to alleviate poverty and improve fishermen's welfare. A number of countries, especially developed countries encourage the elimination of fisheries subsidies through WTO and other countries, especially developing countries opposed the proposal of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…These results also confirmed those of Jara-Rojas, Bravo-Ureta, and Díaz [100], who presented farmer access to subsidies as positively associated with water irrigation technology adoption. According to Notohamijoyo et al [101], in Indonesia, subsidy programs for small-scale fisheries were demonstrated to create benefits to the well-being of the fishers and fisheries' sustainability when focused on fishing vessels, vessel machines, and environmentally friendly fishing gear. From a co-management perspective, unemployment insurance subsidy implementation was suggested by shellfish harvesters to improve fishery sustainability during the closed period in northeast Brazil [102].…”
Section: Discussionmentioning
confidence: 99%
“…These results also confirmed those of Jara-Rojas, Bravo-Ureta, and Díaz [100], who presented farmer access to subsidies as positively associated with water irrigation technology adoption. According to Notohamijoyo et al [101], in Indonesia, subsidy programs for small-scale fisheries were demonstrated to create benefits to the well-being of the fishers and fisheries' sustainability when focused on fishing vessels, vessel machines, and environmentally friendly fishing gear. From a co-management perspective, unemployment insurance subsidy implementation was suggested by shellfish harvesters to improve fishery sustainability during the closed period in northeast Brazil [102].…”
Section: Discussionmentioning
confidence: 99%